Rating of perceived capacity: A proposal to predict adequate levels of physical activity in visually impaired individuals - Barbosa D.G.* (2019)
© 2017 Edizioni minerva medica.BACKGROUND: There are several instruments that are generally used to analyze levels of physical activity (PA) in people with visual impairment. However, few instruments are validated for this population. The purpose of this study was to compare the subjective and objective variables of PA and to propose the use of the Rating of Perceived Capacity (RPC) to evaluate the level of moderate to vigorous physical activity (MVPA) per day in this population. METHODS: Thirty-seven individuals with visual impairment participated in the study (19 blind without light perception and 18 low-vision). For the subjective physical activity evaluation, it was used the International Physical Activity Questionnaire Short Form (IPAQ-SF) and for the objective evaluation, it was used the ActiGraph GT3X+. RESULTS: Among the three analyzed (PA) intensities: moderate physical activity (MPA), vigorous physical activity (VPA) and MVPA, in VPA and MVPA was observed differences between the two methods (P=0.002 and P=0.011 respectively). Furthermore, the concordance between subjective and objective MVPA was not observed (ICC=0.239; P=0.176), and a greater variability of differences in MVPA between the two methods was observed by the Bland Altman scatter plot. However, positive correlation was found between the RPC and MVPA (P=0.470; P=0.003). In addition, in the Receiver Operating Characteristic (ROC) curve analysis, it was verified that values greater than 8 points in the RPC showed a predictive capacity for sufficient levels of objective MVPA (AUC=0.809, sensitivity =66.7, specificity =90.9, P≤0.001). CONCLUSIONS: We concluded that the MVPA per day obtained by IPAQ-SF did not show agreement for the objective MVPA in visually impaired individuals. On the other hand, RPC presented itself as an alternative, practical and accessible tool to predict adequate levels of MVPA per day in this population.